x-3(-1)=3

Simple and best practice solution for x-3(-1)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-3(-1)=3 equation:


x-3(-1)=3

We simplify the equation to the form, which is simple to understand
x-3(-1)=3

Reorder the terms in parentheses
x+(+3)=3

Remove unnecessary parentheses
+x+3=+3

We move all terms containing x to the left and all other terms to the right.
+1x=+3-3

We simplify left and right side of the equation.
+1x=0

We divide both sides of the equation by 1 to get x.
x=0

See similar equations:

| (27b^6)^4/3 | | (2x+16)=(x+14) | | (n^5)^4/5 | | 1.03x=113740 | | 4x+18=2x+54 | | 103x=113740 | | 7/11x=2 | | 3x+24y=12 | | X^2-8x=32 | | 28-2x=13-7x | | 3+30x=15x+21 | | 13+3(3x+8)=8-x | | 2ln(3x-2)+2=0 | | 6z+z=z-4 | | .50x+0.15(30)=27.5 | | 11-14x+28+30x=4x-12+23+6x | | 3x+6=-50-5x | | 36-6x=8-10x | | (1/2x-2)^5 | | 1+9x=-23+x | | 9x(x-2)=4(x+2) | | 2x+24=3+8x-9 | | 10a-50-28(a-2)=14(3a+15) | | 4464=10(p+48) | | 4ln(6x)=2 | | 4+5x=6x+1 | | 11x-1=10x+2 | | 3x=5b | | p=90x-200-x^2 | | 8m^3-24m^2+18m=0 | | 4/16=B | | p=25-0.01s^2 |

Equations solver categories